Who Is Bearing the Burden? Exploring the Role of Albanian International Migration on Education - Dabalen, Andrew (2012)
The literature on migration has documented the benefits of sending migrants abroad, but much less attention has been paid to the adverse consequences of international migration on those left behind. In this paper, we examine the role of international migration on the accumulation of human capital in Albania. We ask whether investment in human capital of children growing up in households with international migrants is higher compared with children in households without migrants. We find that, across various model specifications, international migration has a negative effect on education in Albania, with larger negative effects for females in rural areas.